Mitigasi bencana banjir berbasis sekolah - Vistarani Arini Tiwow; Eko Hadi Sujiono; Sulistiawaty Sulistiawaty (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partnerof this Community Service (PKM) was SMA 5 Parepare. The problems were: (1) lack of knowledge regarding the causes of floods and disaster mitigation, and (2) lack of socialization on flood mitigation.Activities carried out in the form of socialization with the methods used were: lectures, question and answer, and video playback causes flooding. The results achieved were: (1) knowledge of partners increases through socializaion about the importance of environmental sustainability, flooding and various causes, as well as school-based flood disaster mitigation efforts, and (2) Public awareness (students) increases in supporting flood mitigation efforts.